Regulation of glycerol transport genes GUP1 and GUP2 in Saccharomyces cerevisiae - Oliveira, Rui Pedro Soares de (2000)
Apresentação efectuada no XII Congresso Nacional de Bioquímica, na Póvoa de Varzim, em 2000.